2010
DOI: 10.1002/jclp.20688
|View full text |Cite
|
Sign up to set email alerts
|

Rural mental health and psychological treatment: a review for practitioners

Abstract: Practitioners in rural areas face particular challenges in providing psychological services, ranging from disparate rates of mental disorders to unique circumstances in treating special populations. In this article, we discuss the burden of mental disorders in rural areas, current trends in integration of mental health care and primary care, and unique concerns practitioners face in treating two special populations in rural areas (children and families, and older adults and their caregivers). Implications for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
169
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(177 citation statements)
references
References 45 publications
5
169
1
2
Order By: Relevance
“…The internet offers a method for delivering psychological interventions that is time-and resource-efficient, and has the benefit of providing treatment to those who may otherwise lack access to available services [53,54]. Moreover, online interventions have the potential to overcome many of the barriers to help-seeking that depressed individuals have reported in the past, including: cost, a shortage of trained professionals, concerns about anonymity, convenience, perceived stigma, and ease of accessibility [19][20][21][55][56][57].…”
Section: Online Psychological Interventions For Depressionmentioning
confidence: 99%
“…The internet offers a method for delivering psychological interventions that is time-and resource-efficient, and has the benefit of providing treatment to those who may otherwise lack access to available services [53,54]. Moreover, online interventions have the potential to overcome many of the barriers to help-seeking that depressed individuals have reported in the past, including: cost, a shortage of trained professionals, concerns about anonymity, convenience, perceived stigma, and ease of accessibility [19][20][21][55][56][57].…”
Section: Online Psychological Interventions For Depressionmentioning
confidence: 99%
“…For example, these underserved areas display a shortage in medical and behavioral health providers which can impact patient access to health care. Also, stigma regarding the treatment of certain conditions (e.g., depression, sexually transmitted infection) also hinders patient engagement with time-sensitive treatment [1,2]. Research has shown that the use of telemedicine, especially in rural primary care settings, has been able to alleviate patient barriers to care and improve treatment efficiency [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…1 Implementation of integrated primary care in rural areas faces several additional challenges, most notably a higher prevalence of behavioral health conditions and difficulties with "accessibility, availability, and acceptability of mental health services." 18 Rural youth and adults suffer from depression and substance abuse at higher rates than nonrural youth and adults, and they also have a higher rate of completed suicides. 18,19 As of 1999, 87% of mental health professional shortage areas are in nonmetropolitan areas, making access to behavioral health care a major difficulty.…”
mentioning
confidence: 99%
“…18 Rural youth and adults suffer from depression and substance abuse at higher rates than nonrural youth and adults, and they also have a higher rate of completed suicides. 18,19 As of 1999, 87% of mental health professional shortage areas are in nonmetropolitan areas, making access to behavioral health care a major difficulty. 17 The stigma surrounding mental health persists and is especially strong in rural areas; maintaining confidentiality is difficult, as in the classic example of recognizing a neighbor's vehicle parked in a mental health facility's parking lot.…”
mentioning
confidence: 99%
See 1 more Smart Citation